2004
DOI: 10.1074/jbc.m406090200
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of NPC1 to Late Endosomes Involves Multiple Signals, Including One Residing within the Putative Sterol-sensing Domain

Abstract: The NPC1 protein is a multipass transmembrane protein whose deficiency causes the autosomal recessive lipid storage disorder Niemann-Pick type C1. NPC1 localizes predominantly to late endosomes and has a dileucine motif located within a small cytoplasmic tail thought to target the protein to this location. Our data have suggested previously that the protein can reach its correct location in the absence of its cytoplasmic tail, suggesting that other signals contribute to NPC1 targeting. By using various FLAG-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 57 publications
1
30
0
1
Order By: Relevance
“…While these observations complicate efforts to define strict orthologous relationships within this gene family, several sequence features suggest that NPC1a and NPC1b may function equivalently to NPC1 and NPC1L1, respectively. In particular, the findings that NPC1a has greater sequence similarity to NPC1 and that NPC1a and NPC1 (but not NPC1b or NPC1L1) share a C-terminal lysosomal targeting motif suggest that NPC1a may play a functional role that more closely parallels that of NPC1 (Ioannou 2000;Scott et al 2004). Furthermore, the NPC1L1 and NPC1b polypeptides share a putative YQRL Golgi retention signal (Humphrey et al 1993) and no such sequence is found in NPC1 or NPC1a (see supplemental Figure 1 at http://www.genetics.org/supplemental/).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these observations complicate efforts to define strict orthologous relationships within this gene family, several sequence features suggest that NPC1a and NPC1b may function equivalently to NPC1 and NPC1L1, respectively. In particular, the findings that NPC1a has greater sequence similarity to NPC1 and that NPC1a and NPC1 (but not NPC1b or NPC1L1) share a C-terminal lysosomal targeting motif suggest that NPC1a may play a functional role that more closely parallels that of NPC1 (Ioannou 2000;Scott et al 2004). Furthermore, the NPC1L1 and NPC1b polypeptides share a putative YQRL Golgi retention signal (Humphrey et al 1993) and no such sequence is found in NPC1 or NPC1a (see supplemental Figure 1 at http://www.genetics.org/supplemental/).…”
Section: Resultsmentioning
confidence: 99%
“…The NPC1 protein also bears resemblance to the bacterial class of RND permeases and is able to transport fatty acids (Davies et al 2000a), although the importance of this result is unclear as the flux of these species from lysosomes in NPCD cells is unperturbed (Passeggio and Liscum 2005). Consistent with the predicted topology and lysosomal targeting motifs present in NPC1, subcellular distribution analyses indicate that the NPC1 polypeptide is localized to membranes of late endosomes, lysosomes, and the TGN (Garver et al 2000;Scott et al 2004). In conjunction with the cholesterol accumulation phenotype seen upon loss of NPC1 function, these findings strongly suggest a direct role for this factor in the trafficking of sterols through the endocytic/secretory pathway, although precisely how NPC1 mediates these trafficking events is far from clear.…”
mentioning
confidence: 98%
“…NPC1 protein is predominantly located within the late endosomal membrane but is also transiently associated with lysosomes and the trans-Golgi network (10). Multiple peptide sequences within the protein are responsible for targeting to the endosomal compartment (11). Late endosomes are comprised of limiting membranes and internal membranes (12).…”
Section: Biochemical Studies On Npc1 and Npc2 Proteinsmentioning
confidence: 99%
“…2A). To examine whether endosomal localization was required for NPC1 to undergo this modification, we examined effects of cholesterol depletion on the ␦LLNF mutant protein that lacks the C-terminal di-leucine motif and is retained in the ER (Watari et al, 1999b;Scott et al, 2004). As in the case of the P691S mutant, ubiquitylation of this mutant protein was barely affected by cholesterol depletion (Fig.…”
Section: Mutant Proteins Flag-npc1(p691s) and Flag-npc1(␦llnf) Failedmentioning
confidence: 99%